Initial Validation of the Indonesian Version of the RESTQ-Sport-76: A Psychometric Study among Sport Science Students (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
The balance between stress and recovery is essential to maintain sport performance and wellbeing. The Recovery-Stress Questionnaire for Athletes (RESTQ-Sport-76) has been widely used internationally to measure psychosocial dimensions. However, the Indonesian version has not undergone formal psychometric evaluation. This study aimed to conduct an initial validation and reliability testing of the Indonesian version of RESTQ-Sport-76 in sport science students. A cross-sectional quantitative design was used, involving 120 sport science students (74% male, aged 18-23 years) recruited through purposive sampling. The instrument, adapted through forward-backward translation and expert review, was distributed via an online form. Data analysis included item-total correlation for construct validity, Cronbach’s alpha for internal consistency, and confirmatory factor analysis (CFA) using SPSS AMOS to assess model fit. Most subscales showed good validity (r ≥ 0.50) and adequate internal reliability (α ≥ 0.70). The initial CFA indicated suboptimal fit for general stress and recovery dimensions (CFI = 0.666; RMSEA = 0.102), which improved after model revision (CFI = 0.930; RMSEA = 0.055). Similarly, the sport stress and sport recovery model fit improved from CFI = 0.866 to 0.973 after refinement. In conclusion, the Indonesian version of RESTQ-Sport-76 demonstrated satisfactory initial validity and reliability, supporting its use as a preliminary tool for monitoring stress and recovery among sport students. Nonetheless, several subscales, particularly related to conflict/pressure and sleep quality, require further semantic refinement and longitudinal testing before large-scale practical application.